2014
DOI: 10.1002/ijc.28727
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms of CDKN2A (p16) alteration in oral tongue squamous cell carcinomas and correlation with patient outcome

Abstract: CDKN2A (p16) disruption is reported as a frequent event in head and neck squamous cell carcinomas that confers poor prognosis. We investigated the frequency of different potential mechanisms of CDKN2A inactivation in oral tongue squamous cell carcinomas (OTSCC) and their impact on patient outcome. From a cohort of 153 OTSCC patients, 131 formalin fixed paraffin embedded blocks of pre-treatment primary tumours were suitable for further molecular analysis. We assessed CDKN2A (p16) levels by immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Details of the full cohort of 131 patients have previously been described [ 96 ]. The clinical and tumor characteristics of the 115 patients with bisulfite modified DNA available for methylation analyses are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the full cohort of 131 patients have previously been described [ 96 ]. The clinical and tumor characteristics of the 115 patients with bisulfite modified DNA available for methylation analyses are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the methylation sensitive high resolution melting (MS-HRM) results for the panel of interrogated genes is presented in Table 3 , including results from our previous study on CDKN2A [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demokan’s study noted that promoter hypermethylation levels were associated with decreased p16 expression in the tumor samples [ 22 ]. Interestingly, Annette’s study found that 95% (110/116) of OSCC did not overexpress p16, while p16 INK4a promoter methylation was 18% (20/113) [ 50 ]. Human papillomaviruses (HPV) is also an important factor in carcinogenesis of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Four micron FFPE sections from the TMAs or whole slides were stained for p16 using Ventana Ultraview Detection reagents on a Benchmark Ultra instrument (Ventana Medical Systems, Tucson, AZ, USA) as previously described ( Lim et al , 2014 ). In brief, antigen retrieval was performed with CC1 high-pH retrieval solution for 52 min followed by incubation at 36 °C for 32 min in primary antibody (mouse monoclonal p16, Clone E6H4; Ventana Medical Systems) and then detection with UltraView Universal DAB detection kit (Ventana Medical Systems).…”
Section: Methodsmentioning
confidence: 99%